Decentralized Bargaining in a Globalizing Industry: The Automotive Assembly Industry in Australia - Lansbury, Russell; Wright, Chris; Baird, Marian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
This paper examines the impact of enterprise bargaining on employment relations practices in the Australia automotive assembly sector in the context of the globalization of the industry. While there has been convergence towards lean production principles among the four auto assemblers, arising from global trends, there has also been divergence resulting from enterprise bargaining, among other variables. Strong similarities are apparent between the companies in areas such as work organization, skill formation and enterprise governance, whereas there are differences in remuneration and staffing practices. However, it remains to be seen whether decentralized bargaining will continue to yield greater differentiation in employment relations among the automotive manufacturers in an increasingly globalized industry.